Vampires, race, and transnational Hollywoods - Hudson, Dale M., 1965- (Traditions in American cinema., 2017)
The figure of the vampire serves as both object and mode of analysis for more than a century of Hollywood filmmaking. Never dying, shifting shape and moving at unnatural speed, as the vampire renews itself by drinking victimś⁰₉ blood, so too does Hollywood renew itself by consuming foreign styles and talent, moving to overseas locations, and proliferating in new guises. In Vampires, Race, and Transnational Hollywoods, Dale Hudson explores the movement of transnational Hollywood́⁰₉s vampires, between low-budget quickies and high-budget franchises, as it appropriates visual styles from German, Mexican and Hong Kong cinemas and off-shores to Canada, Philippines, and South Africa. As the vampiré⁰₉s popularity has swelled, vampire film and television has engaged with changing discourses around race and identity not always addressed in realist modes. Here, teen vampires comfort misunderstood youth, chador-wearing skateboarder vampires promote transnational feminism, African American and Mexican American vampires recover their repressed histories. Looking at contemporary hits like True Blood, Twilight, Underworld and The Strain, classics such as Universaĺ⁰₉s Dracula and DrÃŁcula, and miscegenation melodramas like The Cheat and The Sheik, the book reconfigures Hollywood historiography and tradition as fundamentally transnational, offering fresh interpretations of vampire media as trans-genre sites for political contestation.